2012
DOI: 10.1021/jp306620b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reduction of SO2 by CO over PtlAum(CO)n: A First-Principles Investigation

Abstract: The catalytic activities, to the reduction of SO 2 by CO, of clusters Pt l Au m (l + m = 2) with or without preadsorbing CO molecules are investigated using firstprinciples density functional theory. We find that the PtAu(CO) n (n = 1−3) clusters show more excellent catalytic properties than either pure metallic catalysts. Preadsorption of CO to the catalysts could effectively avoid platinum-based catalyst sulfur poisoning; as more CO molecules preadsorbed to the catalysts, the energy barriers for the carbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…To this end, there has been a major effort to develop catalysts with the ability to efficiently dissociate SO 2 by reduction to elemental sulfur . Oxide‐supported gold nanoparticles catalyze a variety of reactions, and recent work has been focused on the potential of these catalysts to react with SO 2 , as well as to understand how SO 2 can hinder the ability of the catalysts to perform other reactions .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, there has been a major effort to develop catalysts with the ability to efficiently dissociate SO 2 by reduction to elemental sulfur . Oxide‐supported gold nanoparticles catalyze a variety of reactions, and recent work has been focused on the potential of these catalysts to react with SO 2 , as well as to understand how SO 2 can hinder the ability of the catalysts to perform other reactions .…”
Section: Introductionmentioning
confidence: 99%
“…A larger E des means the catalysts are poisoned by COS (see ref. 26). As the number of pre-adsorbed CO molecules increases (n 4 1), the spin multiplicity of Pt 2 (CO) n turns into a singlet, which weakens the interactions between the COS and the catalyst.…”
Section: The Catalytic Propertiesmentioning
confidence: 99%
“…18,22 Lots of researchers have demonstrated that the Pt/Au alloys and their bimetallic clusters show superior catalytic properties to the individual components. 15,[23][24][25][26][27] However, the real catalytic reaction is a rather complicated process. The understanding of the mechanism of PtAu bimetallic catalysts is still in its initial stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several catalysts, such as Pt-Au bimetallic catalyst [12,14], La 2-O 2 S catalyst [15,16], were developed for the selective reduction of SO 2 . In spite of good catalytic performance in SO 2 reduction to elemental sulphur using CO as an agent, the use of expensive noble metals and rare earth metals as the active components limits the large-scale use of these catalysts.…”
Section: Introductionmentioning
confidence: 99%